Increased Zinc Serum Level: New Clues in Babol Stroke Patients, Northern Iran - Alijan Ahmadi Ahangar; Payam Saadat; Sona Niroomand; Shayan Alijanpour; Reza Sohrabnezhad; Alireza Firozejahi; Mohamad Ali Biani; Fatemeh Arab; Hamed Hosseinzadeh; Sekine Faraji; Jalal Niroomand (Stroke Research and Treatment)
Background. Stroke is the second leading cause of death worldwide. The role of zinc as a new predictor of stroke was considered. Methods. This prospective study was conducted in Ayatollah Rouhani Hospital within a year on 100 stroke and 100 control patients. Findings. The difference in zinc serum level in two groups was significant (deficiency: 3 (3%) in patients versus 20 (20%) in control group, normal: 25 (25%) versus 54 (54%), and increased level: 72 (72%) versus 26 (26%); p<0.001). Difference in zinc serum levels was statistically significant with ischemic heart disease (deficiency: 0 cases (0%), normal: 8 cases (24%), increased level: 24 cases (75%), p=0.003). Increases in zinc serum level were significantly correlated with the frequency of hemorrhagic and ischemic patients (deficiency: 3 (3.3%) hemorrhagic versus 0 (0%) ischemic; normal: 19 (21%) versus 6 (60%), increased level: 68 (75.6%) versus 4 (40%); p=0.025). Regression logistics showed that ischemic heart disease (p<0.001; OR = 28.29, %95 CI: 5.53; 144.87), hyperlipidemia (p<0.001; OR = 0.26, %95 CI: 0.12; 0.56), and zinc serum level (p<0.001, OR = 15.53, %95 CI: 4.03; 59.83) each had a significant role. Conclusions. Babol stroke patients are prone to increased zinc serum level as a new parameter. Ischemic heart disease, increased levels of zinc, and hyperlipidemia were found to be probable predictor factors for stroke in Babol.